2001
DOI: 10.4067/s0717-71782001000100007
|View full text |Cite
|
Sign up to set email alerts
|

Producción y rendimiento reproductivo en Petrolisthes granulosus (Decapoda, Anomura, Porcellanidae) en diferentes localidades del norte de Chile: Una comparación latitudinal

Abstract: La variación latitudinal en la ecología reproductiva de una misma especie constituye información relevante que permite conocer las adaptaciones al ambiente (Sastry, 1970). En el pasado, varios autores han propuesto y discutido la respuesta reproductiva

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
10
0
9

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 27 publications
3
10
0
9
Order By: Relevance
“…A similar latitudinal trend has been observed in other decapods (e.g. Thorson, 1950;Sastry, 1983;Hernáez, 2001); however, to the best of our knowledge, this is the first evidence of such a latitudinal gradient in egg production in galatheids.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…A similar latitudinal trend has been observed in other decapods (e.g. Thorson, 1950;Sastry, 1983;Hernáez, 2001); however, to the best of our knowledge, this is the first evidence of such a latitudinal gradient in egg production in galatheids.…”
Section: Discussionsupporting
confidence: 62%
“…However, life history features might change with latitude in species with a wide latitudinal distribution such as P. monodon. This conclusion is supported by different studies relating latitude to body size (Atkinson and Sibly, 1997;Angilletta and Dunham, 2003), sex ratio (Defeo and Cardoso, 2002;Rivadeneira et al, 2010) and reproductive biology (Hernáez, 2001;Lardies and Wehrtmann, 2001).…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…However, the number of available studies regarding this subject is still limited, which hinders the development of a more complete understanding of the evolution of life-cycle strategies in this highly diverse group of crustaceans (Garcia and Mantelatto 2001). Some studies demonstrated intraspecific differences along latitudinal gradients in the reproductive biology of decapods, including anomuran species (Jones and Simons 1983;Clarke 1987;Wehrtmann and Kattner 1998;Hernáez 2001;Lardies and Wehrtmann 2001;Brante et al 2003;Castilho et al 2007;Terossi et al 2010b). The reasons for the latitudinal cline in reproductive features of marine invertebrates are still under discussion (Clarke 1992(Clarke , 1993Gallardo and Penchaszadeh 2001).…”
Section: Introductionmentioning
confidence: 99%
“…La fecundidad, tradicionalmente definida como el número de huevos liberados por una hembra por desove, o durante un periodo determinado durante su ciclo de vida (Hernáez, 2001), constituye una información valiosa la cual permite estimar el potencial reproductivo de una población y realizar estudios comparativos. El esfuerzo reproductivo usualmente definido como la fracción de la energía que un organismo destina a la reproducción (López et al, 1997), puede expresarse como rendimiento reproductivo (Ro) que expresa la relación entre el peso seco de la masa de huevos y del cuerpo de la hembra (Clarke, Hopkins, & Nilssen, 1991).…”
unclassified